Polydatin attenuates AGEs-induced upregulation of fibronectin and ICAM-1 in rat glomerular mesangial cells and db/db diabetic mice kidneys by inhibiting the activation of the SphK1-S1P signaling pathway. (15th May 2016) - Chen, Cheng; Huang, Kaipeng; Hao, Jie; Huang, Junying; Yang, Zhiying; Xiong, Fengxiao; Liu, Peiqing; Huang, Heqing
Abstract: We previously demonstrated that activation of sphingosine kinase 1 (SphK1)- sphingosine 1- phosphate (S1P) signaling pathway by high glucose (HG) plays a pivotal role in increasing the expression of fibronectin (FN), an important fibrotic component, by promoting the DNA-binding activity of transcription factor activator protein 1 (AP-1) in glomerular mesangial cells (GMCs) under diabetic conditions. As a multi-target anti-oxidative drug, polydatin (PD) has been shown to have renoprotective effects on experimental diabetes. However, whether PD could resist diabetic nephropathy (DN) by regulating SphK1-S1P signaling pathway needs further investigation. Here, we found that PD significantly reversed the upregulated FN and ICAM-1 expression in GMCs exposed to AGEs. Simultaneously, PD dose-dependently inhibited SphK1 levels at the protein expression and kinase activity and attenuated S1P production under AGEs treatment conditions. In addition, PD reduced SphK activity in GMCs transfected with wild-type SphK WT plasmid and significantly suppressed SphK1-mediated increase of FN and ICAM-1 levels under normal conditions. Furthermore, we found that the AGEs-induced upregulation of phosphorylation of c-Jun at Ser63 and Ser73 and c-Fos at Ser32, DNA-binding activity and transcriptional activity of AP-1 were blocked by PD. In comparison with db/db model group, PD treatment suppressed SphK1 levels (mRNA, protein expression, and activity) and S1P production, reversed the upregulation of FN, ICAM-1, c-Jun, and c-Fos in the kidney tissues of diabetic mice, and finally ameliorated renal injury in db/db mice. These findings suggested that the downregulation of SphK1-S1P signaling pathway is probably a novel mechanism by which PD suppressed AGEs-induced FN and ICAM-1 expression and improved renal dysfunction of diabetic models. Highlights: PD evidently suppressed the expression of FN and ICAM-1 in AGEs-induced GMCs and diabetic db/db mice kidneys. PD evidently suppressed protein expression and activity of SphK1 in AGEs-induced GMCs and diabetic db/db mice kidneys. PD evidently suppressed the DNA-binding activity and transcriptional activity of AP-1 in AGEs-treated GMCs. Inhibition of the SphK1-S1P signaling may be a new mechanism underlying the anti-DN effects of PD.